The design of flats (Rusunawa) in Banda Aceh city - Ega Sara (Jurnal Ilmiah Mahasiswa Arsitektur dan Perencanaan, 2020)
The design of flats (Rusunawa) in Banda Aceh city aim to solve the problem of the increasing number of shelter needs due to the increasing number of population in Banda Aceh every year. To prevent the limitation of residential land in the future, it needs residential buildings that can accommodate a lot of space. This design applies "Tropical Architecture" with emphasis on thermal comfort for residents and modify the climate in buildings by harnessing the natural potential that exists in the wet tropics.